Composite silver nanosurfaces of dipole and quadrupole surface plasmon resonances for fluorescence enhancements. (8th November 2021) - Lee, Daedu; Song, Gyounghyun; Pang, Yoonsoo
Abstract: Composite silver colloidal films (SCFs) prepared with the binary mixtures of homogeneous silver nanoparticles of distinct particle size show strong fluorescence enhancements with 4‐dimethylamino‐4′‐nitrobiphenyl (DNBP). The small and large silver nanoparticles with an average diameter of 82 and 186 nm were chosen for the best spectral overlap between the dipole and quadrupole surface plasmon resonance bands of nanoparticles, respectively, and the emission band of DNBP. From the optimal fluorescence enhancements and strong changes of emission kinetics of DNBP, the composite SCFs of homogeneous silver nanoparticles can be applicable to the development of sensitive fluorescence probes for imaging and sensing purposes. Abstract : Composite silver colloidal nanosurfaces synthesized from homogeneous silver nanoparticles largely enhance the fluorescence of a dye in a good spectral overlap with the combined dipole and quadrupole surface plasmon bands.